Structures of fructan and galactan from Polygonatum cyrtonema and their utilization by probiotic bacteria. (1st September 2021) - Zhang, Junyin; Chen, Hulan; Luo, Lan; Zhou, Zhipeng; Wang, Yingxiang; Gao, Tianyu; Yang, Lian; Peng, Teng; Wu, Mingyi
Abstract: Polygonatum cyrtonema is a known tonic herb in Chinese Materia Medica, extensively consumed in China, but the structure and activity of its polysaccharide components remain to be clarified. Herein, two new polysaccharides (a fructan and a galactan) were purified from the dried and the processed P. cyrtonema rhizome, respectively. Structural analysis suggested that the fructan consisted of a (2 → 6) linked β-d -Fru f residues backbone with an internal α-d -Glc p residue and two (2 → 1) linked β-d -Fru f residues branches, and that the galactan was a (1 → 4)-β-d -galactan branched with a single β-d -galactose at C-6 at about every nine residues in its main chain. The bioactive assay showed that the fructan and the galactan remarkably promoted growth of Bifidobacterium and Lactobacillus strains, indicating that they possess prebiotic activity. These findings may help expand the application of the polysaccharides from the tonic herb P. cyrtonema as functional ingredients in food products. Graphical abstract: Unlabelled Image Highlights: Two purified polysaccharides were first obtained from the tonic herb Polygonatum cyrtonemal The fructan consisted of a (2→6) linked β-D-Fru f backbone with an internal α-D-Glc p and two (2→1) linked β-D-Fru f branches The galactan was a (1→4)-β-D-galactan branched with a single β-D-galactose at C-6 at every nine residues in main chain The fructan and galactan had prebiotic effect on Bifidobacterium and Lactobacillus strains